Hadis Pendidikan Anak: Potensi Dasar Anak Sebagai Modal Pengembangan Diri: Hadis Pendidikan Anak: Potensi Dasar Anak Sebagai Modal Pengembangan Diri - Maulidi, Ahmad Riyadh (Ngaji: Jurnal Pendidikan Islam, 2021)
Every child brings good potential when born. For some people, the wrong understanding of children's lives in analogical sentences is like a white paper, forming education done when they reach adulthood. As a result, children seem slow to receive learning culture from their parents. All the excellent potential they brought from birth motivated their parents to educate as early as possible. This good potential has been described in the hadiths related to children's potential. This argument is interesting for the author to convey the meaning of children's potential through the perspective of the hadith. The author uses literature study in the research method by searching for sources related to children's potential in the hadith. The results show that the good potential children carry from birth can be the initial capital on the way to being a godly servant. This is evidenced by several traditions of the Prophet Muhammad Saw, which indirectly mentions the potential of children. These traditions are the hadith narrated by Bukhari numbers 1385 and 5467 and the hadith narrated by Abu Daud numbers 495 and 5105.